Corelation of standard and secondary fetal biometry with gestational age in the second and third trimesters of pregnancy - Apaza Valencia, John (2015)
Objectives: To determine fetal standard and secondary biometry correlation with gestational age in the second and third trimesters. Design: Cross-sectional study. Setting: Hospital III Honorio Delgado, Arequipa, Peru. Participants: Women in second and third trimester of gestation without evidence of disease. Methods: In 140 26.14 year-old pregnant women in the second and third trimesters of pregnancy presenting for routine ultrasound evaluation, fetal standard biometry and secondary biometry were obtained and correlated with gestational age in the second and third trimesters. Standard fetal biometry included biparietal diameter (BPD), head circumference (HC), femur length (FL) and abdominal circumference (AC); secondary biometry included transverse cerebellar diameter (TCD), renal length (RL) and foot length (PL). Main outcome measures: Standard and secondary fetal biometry regression and correlation with gestational age (GA). Results: All biometric parameters correlated with GA. Best correlation existed with FL (r2 = 0.943) and PL (r2 = 0.940) and the lowest correlation with RL (r2 = 0.860). In the third trimester, correlations were lower than in the second trimester, the highest with FL (r2 = 0.756) and PL (r2 = 0.713), and the lowest with RL (r2 = 0.395). Conclusions: In our population, there was good correlation between the standard and secondary fetal biometry with gestational age; femur length and foot length showed the best correlation in the second and third trimesters of pregnancy, and renal length the poorest correlation in the third trimester.